Assessing the anxiety profile of patients undergoing hysterectomy and mastectomy - Manahan, Lydia T. (1994)
Cancer is threatening to many. By the mere mention of the word, anxiety runs down every nerve of any individual regardless of age, creed, race, or sex. Psychosocially, the individual is thrown off balance when diagnosis of cancer is confirmed. Once cancer is diagnosed as the ailment, surgery becomes the most popular intervention often recoursed to by cancer clients. Surgery becomes another psychoniological threat. This causes anxiety because it is an invasive intervention. To profile the anxiety level of clients who had been diagnosed with cancer and who had undergone surgical interventions, this study was conducted with an attempt to answer the following problems questions: 1. What is the anxiety profile of clients who have undergone hysterectomy and mastectomy? 2. Is there a relationship between the clients' manifested level of anxiety and their demographic variables, such as age, educational attainment, civil status, socioeconomic status, and religiosity? 3. Is there level of manifested anxiety related to women's variables such as her role as wife, as mother, and as a house manager? 4. Is the level of manifested anxiety related to the client's medical variables such as tyoe of surgery and length of hospitalization? 5. Is the level of manifested anxiety related to the clients' interpersonal relationship variables i.e. nurse-patient, doctor-patient in informed consent? 6. Is the level of manifested anxiety related to the clients' social support such as the number of persons extending support and the type of support provided? 7. Is there a significant difference in the levels of manifested anxiety between mastectomy and hysterectomy clients the effects of their surgery? These questions leaned on the conceptual framework that anxiety level of clients with cancer and who underwent surgery are affected by several factors grouped according to: - personal sociodemographic characteristics. - women's variables. - medical variables. - interpersonal relationships, and - social support.
From these variables, the research hypotheses were formulated, then tested in correlational and pair-wise comparative statistical analyses pre-set at the level of 95 confidence. Tools utilized in this study consisted of Anxiety Trait Inventory and Anxiety State Inventory Scale which were modified by the investigator. A total of sixty (60) cancer patients, equally divided between those who underwent mastectomy and those who had hysterectomy were drawn out from a purposive sampling scheme confined at the surgical wards of UP-PGH during the months of July to December 1993. Inclusion criteria were: - diagnosed as Stage II-III for breast cancer; - diagnosed stage I and II for uterine cancer; - had undergone corresponding surgery; - within the 31-59 age group; and, - willing to participate in this study. Highlights of the findings are: 1. Respondents of both groups showed moderate level of anxiety at the time of diagnosis as measured by the tool. 2. Surgery did not increase or decrease the existing level of anxiety. 3. Among the variables studied, the predictors to lowering the level of anxiety fo those with breast cancer are: - higher educational attainment, - capability to support, and - bigger number of support. 4. For those with uterine cancer, the predictors to lowering the level of anxiety are: - low score of pre-operative anxiety trait, - being married, and - being employed at time of diagnosis. 5. All the other variables did not have any significant relationship with the level of anxiety for both those with breast and uterine cancer. 6. The study concluded with the realization that the health care professionals, especially nurses and physicians, have a great role to play in the care of the clients with cancer, specifically in lowering their anxiety level. Social support can be maximized through the caring traits of nurses and physicians. This is the time when being there at the bedside, allowing clients to verbalize effect a securing feeling among anxious clients. Research along the field of anxiety-reduction and caring traits of health care professionals can be conducted on a bigger scale among cancer clients, across age groups and between genders.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Cancer -- Psychological aspects; Cancer -- Patients; Anxiety in women